The Influence of Transformational Leadership on Public Service Performance Moderated by Core Values BerAKHLAK in the Bogor City Government - Randy Dwi Pranaputra; A. Sobandi; Syamsul Hadi Senen (Dinasti Publisher, 2025)
The purpose of this study was to analyze the effect of transformational leadership on public service performance and to determine and analyze whether the core values of BerAKHLAK moderate the effect of transformational leadership on public service performance. The research method used in this study is a quantitative research method. The population in this study were all State Civil Apparatus (ASN) working in the Bogor City Government, especially in the public service sector. The number of samples used in this study was 95 respondents, which was determined using the Slovin formula. The data used in this study were primary data, namely by distributing questionnaires boldly through Google Forms. The data analysis technique used was a quantitative data analysis technique using the Partial Least Square (PLS-SEM) method. The results of the study showed that there was a significant effect of transformational leadership variables on public service performance in the Bogor City Government. The core values of BerAKHLAK can moderate the relationship between transformational leadership and public service performance. This means that the core values of BerAKHLAK are moderator variables in this study, so that these values strengthen the effect of transformational leadership on public service performance.